Analysis of the correlation between peripheral blood inflammatory markers and imaging burden of cerebral small vessel disease - Yang, Jiayi; Liang, Zhifeng; Li, Daojing; Wang, Jingru; Mei, Liying; Hu, Liangchen; Han, Rongrong; Zhang, Aimei; Ma, Jinfeng; Zhang, Liangliang; Wang, Chunxia; Li, Hongfang (Frontiers in Neurology, 2025)
BackgroundThe purpose of this study is to explore the relationship between peripheral blood inflammation-related indicators, such as neutrophil count (NC), neutrophil-to-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII), and the imaging burden and subtypes of cerebral small vessel disease (CSVD).MethodsGather relevant indicators from the population who underwent physical examinations at the Affiliated Hospital of Jining Medical University between 2018 and 2023. Evaluate the total burden and various imaging markers according to the comprehensive burden score of cerebral small vessel disease (CSVD). Employ logistic regression analysis to investigate the correlation between neutrophil count (NC), neutrophil-to-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII) with the overall burden of CSVD and its distinct markers.ResultsA cohort of 12,478 patients who underwent physical examinations was initially assembled. Following the application of specific inclusion and exclusion criteria, the study included 1,526 patients diagnosed with cerebral small vessel disease (CSVD) and 6,955 6,955 individuals serving as controls. Logistic regression analysis indicated no significant association between the overall burden scores of CSVD and systemic immune-inflammation index (SII), neutrophil-to-lymphocyte ratio (NIR), or neutrophil count (NC). Nonetheless, within the spectrum of imaging markers for CSVD, a significant correlation was identified between deep microbleeds and SII (p = 0.03), while enlarged perivascular spaces (EPVS) demonstrated a correlation with NC (p = 0.029, p = 0.019).ConclusionThis analysis reveals a correlation between NC and SII with CSCD (especially Deep cerebral microbleeds and EPVS), which has warning implications for the prevention of CSVD.